Bioinspired Rattan-derived SiSiC/zeolite monoliths: Preparation and characterisation - Fey, Tobias; et al. (Microporous and Mesoporous Materials, 2006)
In the present article, a three-step process for the preparation of SiSiC/zeolite composites is presented. Rattan-derived SiSiC composites were obtained via a two-step biotemplating liquid silicon infiltration process (LSI). The LSI process, consisting of pyrolysis of the biotemplates (Rattan stems) followed by reactive infiltration of the carbon preforms with liquid silicon at 1550 degrees C, led to the formation of SiSiC ceramic composites. The SiSiC replicas (59 wt.% of SiC, 40 wt.% of solidified Si, 1 wt.% carbon) faithfully reproduced the macrostructure of Rattan and exhibited an open porosity between 20 and 40 vol.%, with unidirectional parallel microchannels in the range of similar to 100-300 mu m in diameter. In a third stage MFI-type zeolite (Silicalite-1 and ZSM-5) coatings were developed on the SiSiC ceramic supports via a partial conversion of the substrate into zeolite (support self-transformation method). The metallic Si in the support was partially dissolved under hydrothermal conditions in a reaction mixture consisting of deionised water, template (TPABr) and NaOH, but without any external Si-source. The influence of different synthesis parameters in the development of the zeolite coating is discussed in detail. The resulting products were characterised by X-ray diffraction, TGA, N-2 adsorption/desorption and SEM-EDX. The filtrates were analysed by ICP-OES. SEM and adsorption measurements revealed that biomorphic cellular SiSiC/zeolite composites possess bimodal (micro-/macro-) porosity. In the final SiSiC/zeolite composite, a maximum zeolite loading up to 40 wt.% was calculated on the basis of TGA and XRD analyses. Thermal shock tests showed that a good coating adherence to the SiSiC substrate was obtained. In addition, a SiSiC/ZSM-5 monolith was also tested as structured catalyst for n-hexane cracking. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: bioinspired SiSiC/zeolite composites; biomorphic ceramics; MFI zeolite; monolithic reactors; microreactors